PENGEMBANGAN MEDIA DOMINO CARD STATES OF MATTER PADA PEMBELAJARAN IPAS KELAS IV SD - Vico Ali Fairuz Assina; Holy Ichda Wahyuni; Deni Adi Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning media is one of the key elements in supporting learning continuity. The purpose of this research is to produce valid, practical, effective media in the context of learning. This research is a development research (Research and Development), namely the development of learning media in the form of domino card states of matters IPAS Class IV SD with the ADDIE model (analysis, design, development, implementation, and evaluation). The results of the validity test conducted by two media experts showed an average percentage of 94% and also 98% and the category “very valid”. while the test of the material expert reached a percentage of 98% in the same category. For the practicality test, researchers involved teachers and students to conduct a practicality test assessment with the percentage results from teachers and students of 89% in the “very practical” category. The effectiveness test of this media was conducted on grade IV students by conducting a learning outcome test which obtained a percentage of classical completeness of 79% with the category "very effective. Thus, based on these results, the domino card states of matter learning media can be said to be feasible to use because it has been tested for validity, practicality, and effectiveness.